Polycystic Ovary Syndrome: Current Insights Into Etiology, Symptoms, And Treatment Options - H S, Mamatha; Kumar BS, Ashok; N S, Disha; S, Bhargavi (Journal of Neonatal Surgery, 2025)
Polycystic Ovary Syndrome (PCOS) is an endocrine disorder that is prevalent in women in the reproductive age whereby the ovaries have cysts and are accompanied by symptoms that reduce quality of life. They include the following; Irregular menstrual cycles, Hyperandrogenism characterized by hirsutism, severe acne and some alopecia, Polycystic ovaries are seen on ultrasound examination. The cause of PCOS is not fully understood, but it is concisely known to be multiethnic and multifactorial with insulin resistance being considered as the critical precipitating factor. This insulin resistance sometimes results in high levels of insulin, adding to hyperandrogenism and worsening of the PCOS manifestation. Measures for managing PCOS are diverse; medical and additional or alternative therapies are employed. Most of the allopathic management involve the use of hormonal treatments like the combined oral contraceptives for irregular menstruation and lowering of androgen levels, spironolactone for hirsutism among others, and metformin for insulin resistance. Likewise nutritional intercession is vital in handling of metabolic perversion linked to PCOS. Healthy carbohydrates, which carbohydrates with a less glycemic index, fibre and daily exercise help with weight and metabolic issues. Further, herbal medicine has other potential benefits in the form of complementary therapies: spearmint tea, for example vitex (chaste tree) to name a couple may help to reduce the discomfort and rebalance hormones. PCOS suffers should be treated individually according to the distinct manifestations because this integrative approach delivers efficient results in managing ailment. Lifestyle changes coupled with pharmacologic and herbal medications enhance the well-being of women with PCOS as well as the reduction of the associated life threatening complications, giving more reason for a better understanding of this illness. Further studies should be conducted to develop new interventions and optimise patient’s care, especially patients with PCOS.